Univariate Analysis to Examine Predictors of Response to Leukocytapheresis in Ulcerative Colitis Patients. Issue 3 (June 2014) - Nagayama, Koji; Takedatsu, Hidetoshi; Mitsuyama, Keiichi; Yamasaki, Hiroshi; Kuwaki, Kotaro; Yoshioka, Shinichiro; Kobayashi, Teppei; Yamauchi, Ryosuke; Kakuma, Tatsuyuki; Sata, Michio
Abstract Leukocytapheresis (LCAP) is reportedly effective for the treatment of active ulcerative colitis (UC) and is a therapeutic option for steroid‐dependent or steroid‐resistant patients with UC. However, a consensus regarding the use of LCAP for UC patients has not yet been established. Therefore, we analyzed patients' records to identify predictors of response to LCAP therapy and subsequent recurrence. Between October 2001 and March 2011, we recruited 41 patients who had been diagnosed as having UC and had received LCAP therapy. Patients diagnosed with moderate to severe UC with left‐side or total colitis and received LCAP therapy for the first time were enrolled. We retrospectively performed a univariate analysis using the patients' medical records to identify factors affecting the therapeutic effect of LCAP. Body mass index exceeding 18.5 kg/m2 was found to influence the therapeutic effect of LCAP. Male sex was correlated with a rapid response to LCAP treatment and the maintenance of remission. UC patients experiencing their first attack or had an elevated C‐reactive protein level prior to LCAP therapy exhibited a relatively long remission period. In the "after LCAP therapy" group, a low Rachmilewitz endoscopic score, low erythrocyte sedimentation rate, or high white blood cell count was associated with a long remission period. Our results suggest that LCAP should be performed for the treatment of early‐onset UC. LCAP can be expected to induce a long remission period, enabling mucosal healing, although the factors that affected the remission period did not influence the therapeutic effect and responsiveness.